Towards paper-based micro bio-sensing of biomarker anti-mycolic acid antibodies for TB diagnosis - Verschoor, Jan Adrianus (University of Pretoria, 2019)
Dissertation (MSc (Biotechnology))--University of Pretoria, 2019.